Glucose-6-Phosphate Dehydrogenase, ZwfA, a Dual Cofactor-Specific Isozyme Is Predominantly Involved in the Glucose Metabolism of Pseudomonas bharatica CSV86T - Bhavik A. Shah; Sravanti T. Kasarlawar; Prashant S. Phale (Microbiology Spectrum, 2022)
ABSTRACT Glucose-6-phosphate dehydrogenase (Zwf) is an important enzyme in glucose metabolism via the Entner-Doudoroff pathway and the first enzyme in the oxidative pentose-phosphate pathway. It generates NAD(P)H during the conversion of glucose-6-phosphate (G6P) to 6-phosphogluconolactone, thus aiding in anabolic processes, energy yield, and oxidative stress responses. Pseudomonas bharatica CSV86T preferentially utilized aromatic compounds over glucose and exhibited a significantly lower growth rate on glucose (0.24 h−1) with a prolonged lag phase (~10 h). In strain CSV86T, glucose was metabolized via the intracellular phosphorylative route only because it lacked an oxidative (gluconate and 2-ketogluconate) route. The genome harbored three genes zwfA, zwfB, and zwfC encoding three Zwf isozymes. The present study aimed to understand gene arrangement, gene expression profiling, and molecular and kinetic properties of the purified enzymes to unveil their physiological significance in the strain CSV86T. The zwfA was found to be a part of the zwfA-pgl-eda operon, which was proximal to other glucose transport and metabolic clusters. The zwfB was found to be arranged as a gnd-zwfB operon, while zwfC was present independently. Among the three, zwfA was transcribed maximally, and the purified ZwfA displayed the highest catalytic efficiency, cooperativity with respect to G6P, and dual cofactor specificity. Isozymes ZwfB and ZwfC were NADP+-preferring and NADP+-specific, respectively. Among other functionally characterized Zwfs, ZwfA from strain CSV86T displayed poor catalytic efficiency and the further absence of oxidative routes of glucose metabolism reflected its lower growth rate on glucose compared to P. putida KT2440 and could be probable reasons for the unique carbon source utilization hierarchy. IMPORTANCE Pseudomonas bharatica CSV86T metabolizes glucose exclusively via the intracellular phosphorylative Entner-Doudoroff pathway leading the entire glucose flux through Zwf as the strain lacks oxidative routes. This may lead to limiting the concentration of downstream metabolic intermediates. The strain CSV86T possesses three isoforms of glucose-6-phosphate dehydrogenase, ZwfA, ZwfB, and ZwfC. The expression profile and kinetic properties of purified enzymes will help to understand glucose metabolism. Isozyme ZwfA dominated in terms of expression and displayed cooperativity with dual cofactor specificity. ZwfB preferred NADP+, and ZwfC was NADP+ specific, which may aid in redox cofactor balance. Such beneficial metabolic flexibility facilitated the regulation of metabolic pathways giving survival/fitness advantages in dynamic environments. Additionally, multiple genes allowed the distribution of function among these isoforms where the primary function was allocated to one of the isoforms.